2022
DOI: 10.1039/d1tb02695j
|View full text |Cite
|
Sign up to set email alerts
|

In situ generated Fe3C embedded Fe–N-doped carbon nanozymes with enhanced oxidase mimic activity for total antioxidant capacity assessment

Abstract: The synthesis of multifunctional and high catalytic performance Fe3C embedded Fe–N-doped carbon nanozymes for the assay of total antioxidant capacity in food samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…After incubating for 15 min at 35 °C, the UV–vis spectra of mixtures were recorded. With respect to the TAC analysis, AA is usually regarded as a typical model to reflect the TAC, , which also was used to evaluate the TAC of fresh fruits or commercial beverages in this work.…”
Section: Methodsmentioning
confidence: 99%
“…After incubating for 15 min at 35 °C, the UV–vis spectra of mixtures were recorded. With respect to the TAC analysis, AA is usually regarded as a typical model to reflect the TAC, , which also was used to evaluate the TAC of fresh fruits or commercial beverages in this work.…”
Section: Methodsmentioning
confidence: 99%
“…The inherent limitations of natural enzymes, such as high production costs, short shelf life, and low stability, have led many researchers to seek alternatives. Yan et al first reported in 2007 that magnetic Fe 3 O 4 nanomaterials have enzymatic activity, which triggered a boom in nanoenzyme research. Inorganic nanomaterials have been reported to have mimetic enzymatic activities such as oxidase-like, peroxidases, catalases (CATs), and superoxide dismutase, and such nanomaterial-based nanoenzymes have been widely used in biosensors, cancer therapy, energy transfer, and bacteriostatic …”
Section: Introductionmentioning
confidence: 99%
“…Due to the uniform active sites and outstanding catalytic practicability, single-atom catalysts (SACs) have emerged as the new-generation enzyme mimics. Isolated metal atoms with high Gibbs free energy were anchored and stabilized on various supports to form homogenous SACs through many techniques including coordination binding, defect design, and spatial limitation. The isolated metal sites endow SACs with the maximal atomic utilization rate and thus eminent catalytic properties. , Note that the loading amount of active metal sites is the vital aspect of the catalytic capability of typical atomic-scale catalysts. In order to advance the loading effectiveness of metal centers on atomic catalysts, many efforts have been made to investigate the site categories on loading efficiency, including dual atomic sites, multiple active centers, and synergistic cluster/nanoparticle-assisted atomic moieties. Unfortunately, the loading quantity of active centers of homogenous SACs or their composite counterparts hardly surpasses 5 wt %, which inevitably obstructs the further catalysis enhancement of atomic-scale catalysts. Owing to the strict maintenance of the atomic dispersion states, it is difficult to prevent the aggregation of metal atoms in a high loading proportion. It is worth noting that Pt SACs with a loading efficiency of 41.8 wt % were obtained on the basis of the formation of high defect density by a laser-planting strategy.…”
Section: Introductionmentioning
confidence: 99%